Feasibility, Acceptability, and Preliminary Efficacy of an App-Based Mindfulness-Meditation Program Among Older Adults. (14th August 2020) - Mahlo, Leeann; Windsor, Tim D
Abstract: Background and Objectives: Few studies have focused on the utility of mindfulness-meditation for well-being in older adults. The present study investigated the feasibility, acceptability, and preliminary efficacy of an app-based mindfulness-meditation program among older adults. Research Design and Methods: A community-based sample of 46 participants aged between 63 and 81 ( M = 70.85, SD = 4.70) engaged with a 30-day app-based mindfulness-meditation program for 10 min daily on their smartphones. Each meditation session comprised focusing on the breath, mentally scanning the body, monitoring the mind's activity, and cultivating a nonjudgmental orientation toward experiences. Participants completed questionnaires at baseline, day 10, and day 30. Results: On average, participants completed 25 sessions and almost 4 h of application use across the 30 days. Results of linear mixed effects models showed significant improvements in positive affect, negative affect, and life satisfaction across the study interval, but no meaningful change in total mindfulness or perceived stress. Furthermore, relative to high levels of smartphone efficacy, low smartphone efficacy was associated with higher perceived stress and negative affect, and less life satisfaction at baseline; and steeper improvements on these outcomes across the study interval. On average, older adults rated the app-based mindfulness-meditation training as interesting, enjoyable, valuable, and useful. Discussion and Implications: The findings provide preliminary support for the feasibility and acceptability of an app-based mindfulness-meditation program with community-dwelling older adults and demonstrate potential benefits for well-being. Results suggest the value of further research investigating the efficacy of digital mindfulness-meditation interventions for older adults via larger randomized controlled trials.